Ludic Pedagogy: Taking a serious look at fun in the COVID-19 classroom and beyond - Sharon Lauricella; T. Keith Edmunds (Educational Considerations, 2022)
The COVID-19 pandemic has affected deep reflection in higher education classrooms: how do we attract and retain students to (temporary but nevertheless increasing) online learning experiences, how do we keep them at our universities and colleges, and how do we give students a learning experience from which they will remember meaningful information? In this paper, we introduce a new pedagogical framework that we call Ludic Pedagogy. We address the four elements of this model: fun, positivity, play, and playfulness. Each of the elements is described in turn, together with literature outlining how each contributes to a positive classroom environment that helps students engage with and learn course content. Examples of how the authors have used this pedagogical model are included and described. We suggest that instructors consider using the Ludic Pedagogy model so as to improve engagement, learning outcomes, and retention in their classes and broader university/college contexts.
Keywords: pedagogy; student success; student engagement; student retention; fun; play; playfulness; positivity